POLA PENGAWASAN PEMERINTAH DALAM PENYALURAN BANTUAN LANGSUNG TUNAITERHADAP MASYARAKAT MISKINDI KELURAHAN GURABATI KECAMATAN TIDORE SELATAN KOTA TIDORE KEPULAUAN - Kamis, Yusuf (Aksara Public, 2018)
This research was carried out in Gurabati Village, South Tidore Subdistrict, Tidore Islands City. The population made in this study were 12 employees in the Gurabati sub-district office in South Tidore District, Tidore Islands City. The samples used in the study were 12 government employees at Gurabati Urban Village office and 3 Social Service staff and 15 people from the community so that the total sample or respondents were 30 people. The dependent variable includes the distribution of BLT which has indicators: adjusting data for the poor with the applicable provisions; evenly determining the number of BLT received by the poor; the suitability of BLT received by the community according to its provisions; the distribution of BLT is right on target. In analyzing the data obtained in this study using qualitative descriptive techniques that are assisted by frequency tables, it can be stated that the pattern of government oversight in the distribution of Cash Direct Assistance in Gurabati Subdistrict, South Tidore District, Tidore Islands City is measured to be quite good.